Gustavia esmeraldana and G. gracieae: new species of Lecythidaceae from northwestern Ecuador and a key to species of Gustavia in Ecuador - Cornejo, Xavier; Mori, Scott A. (Phytotaxa, 2019)
Gustavia esmeraldana and G. gracieae, two new species of Lecythidaceae known from northwestern Ecuador, are described. Gustavia esmeraldana occurs in the lowlands of the Province of Esmeraldas between 250–650 m and Gustavia gracieae is known from the western side of Pichincha Province between 1250–1700 m. These species are illustrated and their relationships with related species are discussed. A key to the species of Gustavia known from Ecuador is presented.